ERα regulates lipid metabolism in bone through ATGL and perilipin1. Issue 6 (16th April 2013) - Wend, Korinna; Wend, Peter; Drew, Brian G.; Hevener, Andrea L.; Miranda‐Carboni, Gustavo A.; Krum, Susan A.
Abstract A decrease in bone mineral density during menopause is accompanied by an increase in adipocytes in the bone marrow space. Ovariectomy also leads to accumulation of fat in the bone marrow. Herein we show increased lipid accumulation in bone marrow from estrogen receptor alpha (ERα) knockout (ERαKO) mice compared to wild‐type (WT) mice or estrogen receptor beta (ERβ) knockout (ERβKO) mice. Similarly, bone marrow cells from ERαKO mice differentiated to adipocytes in culture also have increased lipid accumulation compared to cells from WT mice or ERβKO mice. Analysis of individual adipocytes shows that WT mice have fewer, but larger, lipid droplets per cell than adipocytes from ERαKO or ERβKO animals. Furthermore, higher levels of adipose triglyceride lipase (ATGL) protein in WT adipocytes correlate with increased lipolysis and fewer lipid droplets per cell and treatment with 17β‐estradiol (E2) potentiates this response. In contrast, cells from ERαKO mice display higher perilipin protein levels, promoting lipogenesis. Together these results demonstrate that E2 signals via ERα to regulate lipid droplet size and total lipid accumulation in the bone marrow space in vivo. J. Cell. Biochem. 114: 1306–1314, 2013. © 2012 Wiley Periodicals, Inc.